Research Abstracts - Sterkowicz, S.
Typical Traumas and General Indications for Motor Rehabilitation of Judoka Results of Competition and Characteristics of Judo Fights Performed During the Olympic Games in Seoul 1988 and in Barcelona in 1992 Analysis Method for Fight Tactics in Judo Motivation of Females and Males Practicing Judo The Special Judo Fitness Test The Technical and Tactical Preparation of Men and Women Judoka Changeable Motivation in Training Cycle of Judoists Differences of Training Between Women and Men Judoka Causes of Emotion in Individual Sports (Gymnastics and Judo) Communication of Teachers with Students in the Training of the ABC of Judo. Summary of "Ju-jitsu: Selected Aspects of Defensive Martial Art" A Comparison of Women's and Men's Technical Education at Judo Tournament Description of Activity of the Participants of the First International Women's Judo Tournament in Poland